2006
DOI: 10.1093/ndt/gfl042
|View full text |Cite
|
Sign up to set email alerts
|

Major effects of delayed graft function and cold ischaemia time on renal allograft survival

Abstract: The results of this analysis of well-matched transplant recipients show that CIT and DGF are the most important predictors of poor short and long-term graft survival. Therefore, in order to improve the long-term survival of renal allografts efforts should focus on limiting CIT and the damage that occurs during this period and on improving our understanding of DGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
226
3
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(247 citation statements)
references
References 16 publications
11
226
3
7
Order By: Relevance
“…Cold ischemia time appears as an important risk factor, consistent with other studies. 2,3 It is a potential target to reduce the risk of DGF. However, most of the other risk factors are predetermined and not amenable to correction.…”
Section: Discussionmentioning
confidence: 99%
“…Cold ischemia time appears as an important risk factor, consistent with other studies. 2,3 It is a potential target to reduce the risk of DGF. However, most of the other risk factors are predetermined and not amenable to correction.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that CIT was the most important risk factor for the occurrence of DGF [6,7], Table 1 and while the DGF rate has decreased it still remains high (68.7-38.5%, p < 0.001) [7]. Among our recipients the DGF rate was relatively low (21.6%), since only 1 out of the 12 grafts had the delayed function, which were retrieved in our centre (8.3%), 3 out of the 23 were received from other hospitals of the city of Brest (13%), and 4 out of the 27 were taken from other regions of Brest zone (14.8%).…”
Section: Discussionmentioning
confidence: 99%
“…In a single-center study, multivariate analysis of 518 renal transplant recipients found that DGF was the principal factor underlying kidney survival at one year [51].…”
Section: Delayed Allograft Functionmentioning
confidence: 99%